SEJARAH DAN NILAI SONGKET PANDAI SIKEK - Silvia Devi (LPPM Universitas PGRI Sumatera Barat, 2015)
Songket is one of weaving creations produced in various countries in Indonesia. The process of making Songket is not easy. It is a difficult and thorough process and needs a long time. Therefore it requires great care and diligence. One area where artisan Songket come from is Nagari Pandai Sikek (Pandai Sikek village) in West Sumatra. Besides Pandai Sikek, there are some other villages such as Silungkang, Koto Gadang, Kubang, Tanjung Sungayang and Batipuh. But the craft of weaving in Pandai Sikek has existed and developed since 1850. Songket weaving skill in Nagari Pandai Sikek still owned by the older generation to the younger generation. These skills cannot be passed on to generations out of Nagari Pandai Sikek, because this is the message left by the ancestors of village communities. In the process of passing on the skill, they are still using methods that have been taught by their ancestors for hundreds of years ago namely by using handloom (Not Weaving Machine Tools). This paper would like to explain about the history of the birth of weaving Songket of Pandai Sikek, processes and manufacturing techniques and values contained in the motives generated in its weaving Songket.